Neonatal screening of developmental dysplastic of hip (DDH) in breech delivered - Yusoff, Zakaria (2007)
Introduction: Developmental dysplasia of the hip (DDH) is a disorder that represents abnormal development or dislocation of the hip secondary to capsular laxity and mechanical factor. It was reported that incidence of DDH in life born babies was very low in Malaysia. However there is no reported study on breech babies in Malaysia. Neonatal screening using Ortolani and Barlow is known to have poor sensitivity which will become better with the experience of examiner. In the current practice, this test is done by medical officer as part of other neonatal screen. We conducted this study to detennine the incidence of DDH in breech babies using Ortolani and Barlow test. We also compared the fmding of examination result between dedicated examiner and routine examiner. Method: This was a cross-sectional study, conducted from October 2005 to December 2006 at Hospital Raja Perempuan Zainab II, Kota Bharu, Kelantan and at Hospital Universiti Sains Malaysia. In the period of the study, 180 babies were examined by dedicated examiner and it is equivalent to 66.9 %of breech deliveries in both hospitals. Out of this, 30 babies were selected to be examined by routine examiner and dedicated examiner which later confirm with ultrasound examinations as the gold standard. The selection was made based on parents consent for ultrasound examination. Result: Out of 180 breech babies, six babies (3.3 %) had positive Ortolani and Barlow test. All 6 babies were among 127 babies delivered through Lower Segment Caesarean Section. Four out of six babies were female and two are male. From 30 selected samples, dedicated examiner detected five babies with positive Ortolani and Barlow test. However routine examiner did not detect any positive Ortolani and Barlow test. Based on ultrasound as gold standard, the dedicated examiner has sensitivity of 0.67 and specificity of0.97. Conclusion: High incidence (3.3%) of positive Ortolani and Barlow test among breech babies supports the need for special attention to this population of patients. A dedicated hip screener for neonatal examination has the ability to detect DDH better than the routine examiner.